FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KECELAKAAN KERJA PADA KARYAWAN INSTALASI GIZI RSUD K.R.M.T WONSONEGORO SEMARANG - Angelo Sefanya Ardida; Daru Lestyanto; Bina Kurniawan (Jurnal Kesehatan Masyarakat, 2019)
Hospital nutrition installation is a vulnerable place that has high accident risk because there are many dangerous types ofzequipment and environmental conditions that could jeopardized the worker. The objective of this research was to analyzed the relations between variables of accident, workplace environment, room temperature, occupational safety and health training, commitment of workers, occupational safety and health procedure, and exhaustion with workplace accident. This research with a cross-sectional approach. The population of this research was food handler of K.R.M.T Wongsonegoro hospital in Semarang amounting to 75 people used simple random sampling technique with 43 respontdent. The data collection was done by fulfilling the accident, , workplace environment, room temperature, occupational safety and health training, commitment questionnaire and also assessing the room temperature using heat stress monitors. Data analysis used the chi-square test. The result showed that there was no relationship between workplace environment, occupational safety and health training, occupational safety and health procedure, exhaustion and there is relationship between room temperature (p-value = 0,012, ???? = 0,05) commitment of workers (p-value = 0,040, ???? = 0,05) with workplace accident on food handler in nutrition installation. The management should educate workers about body fluid requirements for hot environments, conduct routine checks every month through temperature and humidity monitoring sheets, during monthly routine meetings at nutrition installations, it would be better if sharing was done about complaints and sought solutions together.